2020
DOI: 10.1007/s00330-020-06996-2
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance cholangiopancreatography with compressed sensing at 1.5 T: clinical application for the evaluation of branch duct IPMN of the pancreas

Abstract: Objectives To evaluate magnetic resonance cholangiopancreatography (MRCP) with compressed sensing (CS) for the assessment of branch duct intraductal papillary mucinous neoplasm (BD-IPMN) of the pancreas. For this purpose, conventional navigator-triggered (NT) sampling perfection with application-optimized contrast using different flip angle evolutions (SPACE) MRCP was compared with various CS-SPACE-MRCP sequences in a clinical setting. Methods A total of 41 patients (14 male, 27 female, mean age 68 years) un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The optimized CS-BH-MRCP proposed by Song et al showed very interesting results and significantly better demonstrated the communication between the pancreatic cyst and the MPD as compared to the conventional MRCP [32]. With 41 patients included for the evaluation BD-IPMN using MRCP at 1.5T, the short single BH CS-MRCP sequence at 1.5T proposed by Henninger et al demonstrated significantly higher scores in all the diagnostic approach criteria (lesion conspicuity, confidence, communication) compared to the conventional NT-MRCP, a CS-NT-MRCP, and a long single BH CS-MRCP sequences [33]. CS-BH-MRCP sequences that are specifically optimized for pancreatic ducts diseases assessment, could therefore improve the diagnostic performance in this indication.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The optimized CS-BH-MRCP proposed by Song et al showed very interesting results and significantly better demonstrated the communication between the pancreatic cyst and the MPD as compared to the conventional MRCP [32]. With 41 patients included for the evaluation BD-IPMN using MRCP at 1.5T, the short single BH CS-MRCP sequence at 1.5T proposed by Henninger et al demonstrated significantly higher scores in all the diagnostic approach criteria (lesion conspicuity, confidence, communication) compared to the conventional NT-MRCP, a CS-NT-MRCP, and a long single BH CS-MRCP sequences [33]. CS-BH-MRCP sequences that are specifically optimized for pancreatic ducts diseases assessment, could therefore improve the diagnostic performance in this indication.…”
Section: Discussionmentioning
confidence: 97%
“…At 1.5T, in Blaise et al's study, the conventional RT-MRCP acquisition showed a significant superior overall image quality with better visualization of the biliopancreatic ducts, whereas only sharpness was improved with BH-CS-MRCP [24]. In a recent study, a short single BH CS-MRCP sequence, that allowed a reduced acquisition time of 8 s, demonstrated higher scores for image quality, duct sharpness and duct visualization than the conventional NT-MRCP, a CS-NT-MRCP, and a long single BH CS-MRCP (acquisition time of 17 s) sequences, the results being not always significant for all criteria and sequence to sequence comparison [33]. This highlights the potential superiority of the CS-BH-MRCP sequence, even at 1.5T and with an even shorter acquisition time.…”
Section: Discussionmentioning
confidence: 98%
“…20 IPMNs are precursors for cancer with a spectrum of hyperplasia, low-grade dysplasia, and invasive adenocarcinoma. 21,22 In international guidelines, sequential imaging surveillance was proposed with a possible follow-up interval of 6 months, over a period of 2 years, to assess the growth characteristics of suspected BD-IPMN. 23,24 Thus, it is clinically important to determine optimized MRCP protocols for surveillance MR examinations.…”
Section: Discussionmentioning
confidence: 99%